Zinc accounting for different varieties of wheat (Triticum aestivum) under different source and methods of application - GHASAL, P C; SHIVAY, Y S; POONIYA, V; CHOUDHARY, M; VERMA, R K (The Indian Journal of Agricultural Sciences, 2017)
A field experiment was conducted during winter (rabi) seasons of 2013–14 and 2014–15 at ICAR–Indian Agricultural Research Institute, New Delhi to find out zinc accumulation capacity and use efficiencies of different varieties of wheat (Triticum aestivum L.) to zinc fertilization. The zinc concentration in different parts of wheat was found highest in grain followed by spike straw and lowest in straw. Among the tested varieties, highest Zn concentration(40.6 mg/kg) and uptake (189.2 g/ha) in grain was registered in HD 2851 and HD 2967 varieties, respectively. Zinc recovery efficiency of HD 2687 (2.5%) was registered highest among the tested varieties. Highest Zn mobilization efficiency index (ZnMEI) was recorded in HD 2967 variety. Zinc fertilization increased zinc induced nitrogen recovery efficiency (ZniNRE) of all the tested varieties to the tune of 7.4–12.7%. Application of Zn in wheat crop increased Zn concentration in grain by 7–12%. Uptake of Zn was increased 5.2–5.6% in soil + foliar application in comparison to soil application alone. The highest Zn concentration and uptake in grain, and Zn use efficiencies were recorded with the application of 1.25 kg Zn/ha through Zn-EDTA as soil application + 0.5% foliar spray at maximum tillering and booting stage.